2014
DOI: 10.3390/ijerph111010790
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Survival of Glioma Patients with Astrocytoma Grade IV (Glioblastoma Multiforme) Associated with Long-Term Use of Mobile and Cordless Phones

Abstract: On 31 May 2011 the WHO International Agency for Research on Cancer (IARC) categorised radiofrequency electromagnetic fields (RF-EMFs) from mobile phones, and from other devices that emit similar non-ionising electromagnetic fields, as a Group 2B, i.e., a “possible”, human carcinogen. A causal association would be strengthened if it could be shown that the use of wireless phones has an impact on the survival of glioma patients. We analysed survival of 1678 glioma patients in our 1997–2003 and 2007–2009 case-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 22 publications
(34 reference statements)
2
24
0
1
Order By: Relevance
“…We analyzed survival of 1,678 glioma patients in our 1997–2003 and 2007–2009 case-control studies [55]. Use of wireless phones in the >20 years' latency group (time since first use) gave a reduced survival yielding hazard ratio (HR) = 1.68, 95% CI = 1.23–2.29 for glioma; see Table 12.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed survival of 1,678 glioma patients in our 1997–2003 and 2007–2009 case-control studies [55]. Use of wireless phones in the >20 years' latency group (time since first use) gave a reduced survival yielding hazard ratio (HR) = 1.68, 95% CI = 1.23–2.29 for glioma; see Table 12.…”
Section: Resultsmentioning
confidence: 99%
“…Tumour promotion from RF radiation might give earlier symptoms leading to surgery. For 144 (63%) of the 228 cases with low-grade astrocytoma it was possible to calculate tumour volume based on CT/MRI scans [55]. This gave for cases exposed to wireless phones ( n = 121) median volume = 25.1 cm 3 (mean = 37.7, range = 0.15–179.6) compared with unexposed cases ( n = 23) median volume = 18.3 cm 3 (mean = 33.1, range = 0.79–125.7).…”
Section: Resultsmentioning
confidence: 99%
“…A fraction of this energy is absorbed by the biological tissues in close proximity to the emitting antenna, in particular the auricular region and the underlying temporal lobe at a maximum specific absorption value of 2 W/kg [5]. A recent analysis from Carlberg and Hardell [6] revealed decreased survival for patients with glioma, in particular astrocytoma grade IV with long-term use of wireless phones. With mounting concerns about the adverse health effects as a result of increased exposure to RF-EMF, the IARC classified electronic devices, including mobile phones, which emit RF-EMF as group IIB, BPossibly carcinogenic to humans^ [15].…”
Section: Cellular Phones and Rf-emfmentioning
confidence: 97%
“…In glioma, the situation seems to be similar to the whole brain tumor, there were not any strong evidence showed that there was a relationship between glioma morbidity and mobile phone use [2,4,8,9,11,16,23,27,30]. But with the rising of glioma malignant degree, the level III to IV glioma seems to be associated with the use of mobile phone [8,23].…”
Section: ) Gliomamentioning
confidence: 99%
“…But with the rising of glioma malignant degree, the level III to IV glioma seems to be associated with the use of mobile phone [8,23].…”
Section: ) Gliomamentioning
confidence: 99%